(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this research work, a new bis-carbamate was synthesized on the basis of cresol, a reaction mechanism was proposed, which is produced with raw materials, energyefficient, environmentally friendly, waste-free and with high efficiency, and theoretical and practical elemental analyzes were conducted. According to the results, it was proved that the elements in the bis-carbamate molecule are actually present in the molecule and the theoretically calculated atomic shares are close to the practically determined results.